(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Eastern philosophical traditions and Western nutrition related treatments both use chakras. The idea of chakras was formerly thought to be intended for spiritual activity such as kundalini sadhana. Numerous scientific studies on chakra have been published, covering topics with a strong connection to anatomy, physiology, and psychology. The body's energy centres, or chakras, are where the flow of cosmic energy enters the body. In the human body, there are seven chakras. It is connected to the body's primary nerve plexus anatomically, and endocrine glands are connected to it medically. There is evidence that chakras might produce electromagnetic radiation.